Intervensi Tuhan dalam Keterlibatan Orang tua terhadap Gaya Belajar Generasi Pembelajar Mandiri (Homeschooling) - Chanita Christie (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
The success of the child's growth and development process is an important task for parents in accompanying and guiding children to reach the top of the destiny of every talent, passion and longing to be realized. With world conditions that are not getting better, even if technology is getting better and even starting to replace the roles and functions of humans in carrying out the process of daily activities. It really creates a lot of new problems, especially for the future generations of God's church in the future. Parents as the holder of an important role in the process of growth and development and formation of children's character are expected to become a dependent place for children in the world as representatives of God on earth. The author uses the literature study method to describe the form of God's intervention in parental involvement in the learning style of the Self-Learning Generation (Homeschooling). Through literature studies by reading books, the author can formulate a useful view of God's intervention in parental involvement in the Learning Style of the Independent Learning Generation (Homeschooling)